Predisposition to superimposed preeclampsia in women with chronic hypertension: endothelial, renal, cardiac, and placental factors in a prospective longitudinal cohort. (2nd July 2020) - Bramham, Kate; Villa, Pia M.; Joslin, Jennifer R.; Laivuori, Hannele; Hämäläinen, Esa; Kajantie, Eero; Räikkönen, Katri; Pesonen, Anukatriina; Seed, Paul; Dalton, R Neil; Turner, Charles; Wong, Max; et al.
ABSTRACT: Objective: To assess the contribution of maternal and placental factors to the development of superimposed preeclampsia in women with chronic hypertension. Methods: Endothelial and renal function markers were serially assessed in 90 pregnant women with chronic hypertension and controls. Results: Syndecan-1 concentrations were lower at 26–27 +6 weeks in women with chronic hypertension who subsequently developed superimposed preeclampsia compared with those who did not. Decreased PlGF and raised urine albumin:creatinine ratio were also associated with development of superimposed preeclampsia. Conclusion: Decreased syndecan-1 and PlGF concentrations implicate endothelial glycocalyx disturbance and reduced placental angiogenic capacity, respectively, in the pathophysiology of superimposed preeclampsia.